Citizens Assembly - BYRNE, ELAINE (My University, 2011)
We the Citizens set out with optimism, and indeed hope, to test the value to our democracy of including citizens more directly in decision-making. That hope has been truly vindicated. We now have unequivocal proof that citizens? assemblies will work in this country, as they have in many others. We have shown that when you give people objective information and the opportunity to deliberate, not only do they make informed decisions, they also feel a greater connection to the democratic process.
PUBLISHED
Keywords: participatory democracy; citizens assembly